THU0603 Disease burden of knee osteoarthritis patients undergoing joint replacement compared to matched controls: a population-based analysis of a dutch medical claims database. (15th June 2017) - Nielen, JTH; Boonen, A; Dagnelie, PC; Bemt, B van den; Emans, P; Lafeber, F; Spil, WE van; Vries, F de; Welsing, P
Abstract : Background: Knee osteoarthritis (OA) is a progressive joint disease generally associated with increasing pain. In severe symptomatic knee OA, knee prosthesis (KP) can improve health-related quality of life. In the Netherlands, the incidence of KPs and KP revisions has increased, but health care costs related to these procedures over time and their determinants are unknown. 1 Objectives: To provide estimates of age and sex-specific incidence of KPs, revision KPs, and prosthesis complications in patients with knee OA. To determine average annual health care costs of patients undergoing KP compared with matched controls in the Netherlands, and to understand drivers of costs. Methods: All KPs in knee OA patients in the Achmea Health Database were identified and matched by age, sex, and region to a maximum of four controls. Incidence rates of KPs, KP revisions, and their complications (/1000 persons) from 2006–2013 were determined. Annual health care cost and excess costs compared to matched controls, preceding, during and after surgery were calculated and associated factors evaluated using longitudinal regression analysis. Results: The incidence of KPs, KP revisions, and complications increased between 2006 and 2013. This increase was strongest in younger age categories and in men (Table 1 ). Annual health care costs slightly increased up to the year of surgery, with highest costs in the year of surgery. Post-surgery costs remained slightly higher than pre-surgery costs. High post-surgery costs were mainly associated with subsequent KPs. Other factors associated with high excess costs were younger age, female gender, and complications. Conclusions: These results underscore the increasing burden associated with severe knee OA, especially in younger age categories. Improved guidelines aimed at avoiding complications and revisions are required to counteract this trend. References: Dutch Arthroplasty Register (LROI). Arthroplasty in the Picture, Annual Report of the Dutch Arthroplasty Register. 2014. Disclosure of Interest: None declared